Site Selection for the Citronella Oil Distillation Unit at Rambatan Subdistrict Tanah Datar Regency - Alexie Herryandie Bronto Adi; Eri Wirdianto; Felia Devina Amadea; Desto Jumeno; Reinny Patrisina (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
The Sarasah Village Cooperative (KUD Sarasah) located in Nagari III Koto, Rambatan Subdistrict, Tanah Datar Regency plans to build a citronella oil distillation unit. The decision about the location where to build a factory is a strategic decision that needs to be considered carefully, because it involves a large amount of investment and has a long-term impact. This study aims to select the location of the construction of citronella oil distillery. The method used in this research is the Analytical Hierarchy Process. The conclusion that can be drawn regarding the most strategic location for the construction of a citronella oil production house is Aur Serumpun with a weight of 47.9% whereas the Long-Term aspect is the most influential criterion with a weight of 43.4%. KUD Sarasah yang berlokasi di Nagari III Koto, Kecamatan Rambatan, Kabupaten Tanah Datar berencana membangun rumah produksi penyulingan minyak serai wangi. Keputusan tentang lokasi tempat pendirian pabrik merupakan keputusan strategis yang perlu dipertimbangkan secara cermat, karena menyangkut investasi dalam jumlah besar dan memiliki dampak jangka panjang. Penelitian ini bertujuan untuk memilih lokasi pembangunan rumah produksi minyak serai wangi. Metode yang digunakan di dalam penelitian ini adalah Analytical Hierarchy Process. Kesimpulan yang dapat diambil terkait lokasi yang paling strategis sebagai tempat pembangunan rumah produksi minyak serai wangi adalah di Aur Serumpun dengan bobot sebesar 47,9% dimana aspek Jangka Panjang adalah kriteria yang paling mempengaruhi keputusan penentuan lokasi dengan bobot 43,4%.